PERANCANGAN SISTEM INFORMASI KELENGKAPAN PENGISIAN FORMULIR INFORMED CONSENT DI RS AL ISLAM BANDUNG - YANUAR, YUDHI (Politeknik Dharma Patria Kebumen, 2017)
This study aimed to determine medical action approval form completeness (informed consent) information system design using Microsoft Visual Studio 2010 usage in Rumah Sakit Al Islam Bandung. The research used qualitative method with descriptive approach. While data collection techniques used by direct observations, interviews and completed with a literate review that had a relationship to the subject matter. The development method used was Waterfall. From making this information system the writer used programming language Microsoft Visual Studio 2010 and storage of data using Microsoft Access 2007. From the results conducted there were some problems found, such as:lack in socialization of standard operating procedure for informed consent making, many informed consent forms are still not filled in completely, this is unfortunate given the importance of legal aspects contained in informed concent and, proses of analyzing for completeness informed consent form are still uses Microsoft Excel, so that analysis time becomes longer. The suggestions were given by: (1). Socializing the standard operating procedure of making an informed consent to the relevant officers;(2).Developinga new information system for the data processing analysis the completeness of informed consentfilling for producing reports more accurate and time efficiency in the analysis process.